Effect of planting time and density of Corn, Zea mays L on growth and yield of Taro Colocasia esculenta (L.) Schott var. Antiquorum under policulture system - Retno Tri Purnamasari (Gontor AGROTECH Science Journal, 2016)
The aim of research are to study effect of planting time and plant density of corn to growth and yield of taro using policulture system. The research carried out at September 2012- Juli 2013 in Landungsari Village, Malang. Research applied with split plot design, where planting time as main plot consisting: 30 days before taro planting, same time taro and corn planting and 30 days after taro planting. The density between subplots are 15.000 plants/ha, 29.000 plants/ha and 43.000 plants/ha which repeated three times. Result showed the best planting time in policulture of taro and corn is planted corn 30 days afer planted taro, taro yield 14,12 ton/ha. The corn best density is 15.000 plant/ha which resulting yield 16,13 ton/ha.